Investigation of implementation of QAM optical transmission - Hong, L.L.; Geok, T.K.; Reza, A.W. (Natl Inst Optoelectronics, 2010)
This study investigates the possibility of implementation of quadrature amplitude modulation (QAM) format for optical communication system. In this study, we show different ways of QAM analysis through the constellation diagram and the 16-level eye signal using OptSim (TM). The implementation of QAM is also verified using OptiSys (TM) with the 64-level eye signal. The obtained results analysis shows that, both configuration yield the same QAM results and ensure successful implementation of QAM.